Performance nutrition : applying the science of nutrient timing - Austin, Krista, 1977-; Seebohar, Bob (Champaign, IL : Human Kinetics, 2011)
Blends theory with applied content and real-life examples to help nutritionists, coaches, and athletes design nutrition plans based on each athlete's individual needs and the specific demands of the sport
Principles of nutrient timing -- Assessing sport performance -- Psychology and sport nutrition -- Functionality of foods -- Timing fluid intake -- Macronutrient timing strategies -- Nutrition periodization -- Nutritional supplementation -- Nutrient timing in changing environments -- Competition day
Keywords: Athletic Performance -- physiology; Nutritional Physiological Phenomena; Dietary Supplements -- standards